Pre-school teachers - Oakland Unified School District, CA.; Oakland Unified School District, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
The teacher is the key person in implementing the curriculum, the training of parent aides, and adult education. In school he is responsible to the principal and attends staff meetings and school functions. His responsibilities to the preschool project include attending and participating in staff and inservice meetings, teaching adult education classes, executing and developing curriculum. At the center he is responsible for supervising and training the aides, keeping records, conducting parent conferences and visits. He selects and prepares materials and guides aides in the use of these materials. He holds daily evaluation sessions and maintains a professional library for the use of aides and parents. He plans and teaches in the adult education classes. The books to be included in the preschool professional library are listed.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Child Development Centers; Instructional Materials; Library Materials; Paraprofessional Personnel; Parent Participation; Preschool Teachers; Teacher Responsibility; Teacher Role; California (Oakland)